Insect Diversity in Dramaga Protected Forest Area Bogor West Java - Al Khairina, Amelia Rizqia; Sri Wahyuni, Dwi; Meilisha Putri Pertiwi; Feri Rahman (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2025)
Dramaga Protected Forest is a good habitat for various fauna, including insects. Insects have a positive role as pollinators, decomposers, predators and environmental bioindicators, and have a negative impact as pests. Insects have a wide habitat distribution, such as the surface of the ground or underground, fresh water, air, mud, remains of organisms, and parasites on various plants and animals. The presence of insects can be influenced by environmental conditions as their habitat. Therefore, this study aims to determine the diversity of insects in the Dramaga Protected Forest. The study was conducted in the Dramaga Protected Forest with four research methods, namely Pitfall Trap, Sweep Net, Yellow Sticky Trap and Active Searching. Insect catch data were analyzed for diversity index, evenness index and dominance index. The results of this study were a total of 1359 insect individuals consisting of 14 families. The diversity of insects with the four research methods was relatively low because there were dominant families, namely Formicidae, Acrididae, Blattelidae and Cicadellidae. It can be concluded that the determination of insect diversity is more effective using the Sweep Net method. The results of abiotic measurements at the research location showed optimal conditions so that the Dramaga Protected Forest has a good habitat for insect life.